Rahnella aquatilis Sepsis in a Premature Newborn - ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA (HINDAWI LTD, 2015)
Rahnella aquatilis is an infrequently isolatedGram-negative rodwithin the Enterobacteriaceae family. The organism's natural habitat is water. The organism is rarely isolated from clinical specimens and it seldom causes infection in immunocompetent individuals. Here we present a one-month-old boy who was born prematurely at 27th week of gestation by cesarean section with a birth weight of 730 g. He developed sepsis caused by Rahnella aquatilis during the treatment for ventilator associated pneumonia due to Stenotrophomonas maltophilia with ciprofloxacin. He was successfully treated with a combination of amikacin plus meropenem. Although R. aquatilis is one of the saprophyticus organisms, it may cause life-threatening infection in newborn.
Keywords: BACTEREMIA; IDENTIFICATION; INFECTION; TRACT